(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Financial sector liberalization in Kenya and the far world has created an enormous spectrum from which Savings and Credit Cooperative Societies (Saccos) can raise finances from. This has coincided with a period of good performances for a number of Saccos. However, there is no certain indication of a link between the good performance and the financing diversification; it is not clear whether those Saccos who have diverse financing sources perform any better than those who rely on their members savings. This paper therefore sought to establish the effect of financing diversification on the performance of Saccos by answering the question; does financing diversification affect the performance of a Sacco? The study used a descriptive correlational design with the study population being all Kenya Union of Savings and Credit Cooperatives (KUSCCO) member Saccos registered in Kakamega County. Data was collected from a key informant in every Sacco using a questionnaire and analysed using both descriptive and inferential statistics. Descriptive analysis was done to identify any trends and dispersions in the data while Karl Pearsons zero order coefficient of correlation was used to determine the nature of relationship between financing diversification and Sacco performance. Regression analysis was done to model the relationship between financing diversification and Sacco performance.Â The study found out that financing diversification had a significant positive effect on Sacco performance. The study has, however, recommended further researches to establish the risk implications of financing diversification on Saccos.